MINAT DAN PERILAKU WIRAUSAHA SISWA KELAS XI JURUSAN PEMASARAN YANG MENGIKUTI PRAKTIK BISNIS PADA MATA PELAJARAN PENGELOLAAN BISNIS RITEL DI SMKN 1 GOWA - AGUS; THAMRIN TAHIR; MUHAMMAD HASAN; MUHAMMAD DINAR; TUTI SUPATMININGSIH (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to determine the interests and behavior of class XI students majoring in marketing at SMKN 1 Gowa in the academic year 2020/2021 after participating in the entrepreneurship program. This research approach uses a qualitative descriptive approach. In collecting data, researchers used observation, documentation and in-depth interviews with research subjects. Based on the results of the research conducted by the author, it shows that the interest and behavior that grows in students majoring in marketing at SMKN 1 Gowa include the desire (motive) to feel happy, attention and entrepreneurial motivation, the emergence of student discipline can be seen by the behavior of the participants. students who can manage their time properly, namely managing study time, time to produce products to be sold, and can get to school properly and not late, the emergence of self-confidence and optimism, task and result oriented, leadership spirit, future-oriented. Then the interest of students who have a desire in themselves to maintain their business and will develop in the future and be able to compete with other entrepreneurs.